Hildenbrandia ardreae sp. nov. (Rhodophyta), recorded before as Hildenbrandia dawsonii (nom. inval.) - Pedroche, Francisco F. (Phytotaxa, 2024)
Four species of the red algal genus Hildenbrandia have been recorded from Pacific Mexico: H. dawsonii reported on the west coast of Baja California and Jalisco; H. occidentalis with one record from the west coast of Baja California; H. prototypus occurring all along the coast, including the Gulf of California; and the most common and abundant species, H. rubra from Pacific Baja California to Oaxaca, in tropical Pacific Mexico. All four species have been studied morphologically and molecularly using representative specimens. The molecular status regarding the phylogenetic position of H. dawsonii in relation to other species is unclear. H. dawsonii nomenclatural status was analyzed, and additional material from the University Herbaria at UC-Berkekley (UC) was reviewed. Hildenbrandia dawsonii is an invalid name because its alleged basionym (Hildenbrandia canariensis var. dawsonii) is invalid. Therefore, a new species is described: Hildenbrandia ardreae sp. nov., selecting a Dawson specimen from Punta Norte, Cedros Island, Baja California, as the holotype. Furthermore, morphological characters, once used as diagnostic at the species level, are considered irrelevant. The new holotype proposed in this study shows the same characteristics stated by F. Ardré in her original publication (1959) and could be a potential source for DNA extraction for comparative studies.